2010
DOI: 10.1093/cvr/cvq067
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/frizzled signalling modulates the migration and differentiation of immortalized cardiac fibroblasts

Abstract: The results indicate that myofibroblast migration and differentiation, but not proliferation, can be modulated by interventions in Wnt/Fzd signalling. Therefore, Wnt/Fzd signalling may serve as a novel therapeutic target to ameliorate wound healing after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 47 publications
2
51
1
Order By: Relevance
“…However, some discrepancy exists, based on another report that failed to demonstrate increases in a-SMA expression upon the stimulation of fibroblasts with Wnt3a, despite increased migration (41). Moreover, another study showed decreased expression of smooth muscle a-actin after stimulation with Wnt3a (42). The causes of these disparate results are not clear, but seem to suggest that the functional outcome of the activation of the Wnt/b-catenin signaling pathway may be cell type-specific and context-specific.…”
Section: Discussionmentioning
confidence: 99%
“…However, some discrepancy exists, based on another report that failed to demonstrate increases in a-SMA expression upon the stimulation of fibroblasts with Wnt3a, despite increased migration (41). Moreover, another study showed decreased expression of smooth muscle a-actin after stimulation with Wnt3a (42). The causes of these disparate results are not clear, but seem to suggest that the functional outcome of the activation of the Wnt/b-catenin signaling pathway may be cell type-specific and context-specific.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 We tested seven different transfection reagents on cardiac fibroblasts with eGFP mRNA, and all of the reagents had very low transfection efficiency, except for lipofectamine 2000 (described henceforth as lipofectamine) which had a 20% transfection efficiency ( Figure S1). However, lipofectamine caused severe cell damage after 1 week of daily transfection, which is too short a period to induce direct cardiac reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional mRNA transfection methods have low efficiency and high toxicity for primary cardiac cells. 15,16 In addition, the toxicity of transfection reagents is a critical issue for cellular reprogramming because reprogramming requires multiple transfections over a period of weeks. 4,17 In this report, we present the demonstration of mRNAinduced cardiomyocyte-like gene expression in cardiac fibroblasts that were transfected with cardiac reprogramming factors in a new mRNA transfection system, termed C-Lipo, composed of a heart-targeting peptide (CRPPR-R9) and lipofectamine.…”
Section: Lee Et Almentioning
confidence: 99%
“…Other factors that contribute to myofibroblast differentiation include mechanical tension and ED-A fibronectin (Tomasek et al, 2002) and more recently, roles for Type VI collagen (Naugle et al, 2006) and Wnt/frizzled signaling (Laeremans et al, 2010) have been described in CF. Although not particularly well studied in the heart, there is evidence that TGF-induced differentiation of myofibroblasts from non-cardiac sources can be opposed by the action of proinflammatory cytokines, including IL-1 and TNF (Shephard et al, 2004;Liu et al, 2009).…”
Section: Myofibroblast Phenotypementioning
confidence: 99%